MAKNA UNGKAPAN BENTUK NEGATIF (HITEIKEI HYOUGEN) DITINJAU DARI HIPOTESIS SAPIR & WHORF DALAM BUKU AJAR MINNA NO NIHONGO I - Suyanti Natalia (Jurnal Ilmu dan Budaya, 2019)
The objective of this research is to review negation expression for conversation in Minna no Nihongo I, Japanese textbook by Sapir-Whorf Hypothesis. Sapir-Whorf Hypothesis is a hypothesis which shows an interrelationship between language and the mind. In Japanese the relationship between the mind and language has created a language reality in which language influenced by the cultures of the Japanese society. The influencing cultures for example are to show friendliness, modesty and others or a part of the public humility face. The negative form expression is represented by words which shows kind words in the ordinary style of the Japanese Language and kind of words in Japanese communication style. The use of negative expression is based on who is talking to whom, from which he or she comes, and what is the status of the speaker and the hearer. The correct use of the expression reflect an understanding of the culture on Japanese society